2016
DOI: 10.1016/j.jhep.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus mutations associated with ribavirin treatment failure result in altered viral fitness and ribavirin sensitivity

Abstract: Ribavirin is the most common treatment for chronic hepatitis E and is mostly effective, although some cases of ribavirin treatment failure have been described. Here, we report on a particular case of ribavirin resistance and investigate the underlying causes of treatment failure. Mutations in the viral polymerase, an essential enzyme for viral replication, appear to be responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(167 citation statements)
references
References 35 publications
(56 reference statements)
6
161
0
Order By: Relevance
“…135 In this case, although HEV RNA was undetectable after bition. 136 The calcineurin inhibitors (tacrolimus, ciclosporin A) have also been shown to have a pro-proliferative effect, in contrast to mycophenolate mofetil which inhibits HEV replication in vitro.…”
Section: Medical Therapymentioning
confidence: 66%
“…135 In this case, although HEV RNA was undetectable after bition. 136 The calcineurin inhibitors (tacrolimus, ciclosporin A) have also been shown to have a pro-proliferative effect, in contrast to mycophenolate mofetil which inhibits HEV replication in vitro.…”
Section: Medical Therapymentioning
confidence: 66%
“…Here, Todt et al found that, in addition to G1634R, mutations K1383N, D1384G, V1479I and Y1587F (all located within the polymerase domain) were selected during RBV treatment in non-responder patients. In a similar recent study, Debing et al 8 observed by deep sequencing an increasing number of mutations selected along the HEV genome during RBV treatment of one patient with chronic hepatitis E. Interestingly, these authors also identified mutations G1634R and K1383N, as well as another one, that is, Y1320H.…”
mentioning
confidence: 67%
“…In summary, the elegant work by Todt et al 5 published in this issue and the study by Debing et al 8 published elsewhere provide new insights into the antiviral mechanism of RBV as well as the evolution of HEV quasi-species during RBV therapy. When used to treat chronic hepatitis E, RBV applies mutagenic pressure on the viral genome, which may result in viral elimination and may also lead to the selection of resistant variants in patients who do not respond .…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, the emergence of K1383N mutations and their association with an overall increase in viral heterogeneity in several patients, is shown reversible upon RBV cessation [24,26].…”
Section: Therapeutic Interventions and Drug Failurementioning
confidence: 98%